The effect of oil price changes on the automobile industry in Malaysia / Mohd Zulfahmi Mansur - Mansur, Mohd Zulfahmi (2007)
Since the bullish price of oil in 2004, lots of car manufacturer faced a problem regarding their car sales. Their targeted car sales could not be achieved since people are more concerned about the usage of petrol due to the increasing oil prices. Thus, do the changes in oil price affect the car sales and demand? There have been numerous theoretical arguments made and empirical analyses done but there still seems to be no absolute solution to the question the true relationship of oil price with Malaysia automobile sector. This study is conducted to determine the relationship between oil price changes in Malaysia with the car sales. Based on the data from 2000 until 2006, this study was done towards Malaysian oil price and the car sales considering four type of top seller car in Malaysia which is ( Proton, Perodua, Toyota and Honda) as a dependent variables in other to determine whether the relationship between those variable are significant or not.